Construction of a virtual usability laboratory for conducting user tests during remote attendance (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2024)
One of the educational challenges arising from the COVID-19 pandemic was the adaptation of theoretical-practical or practical courses to virtual formats. In this context, the Human-Computer Interaction (HCI) course in the Systems Engineering Program at the University of Cartagena faced the challenge of developing user testing, involving conducting tests with end-users in a controlled environment or usability laboratory. This article contributes by presenting the design and implementation of a virtual academic usability laboratory for conducting user tests. The proposed laboratory was built and evaluated based on practices undertaken by students in the aforementioned HCI course. This laboratory aims to serve as a reference for conducting usability tests in both academic and business settings.
Keywords: Usability laboratory; usability tests; user test; usability